Grammar Usage in Public Speaking - Witri Handayani (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
Many people think that it is difficult to speak grammatically correct since grammar has so many rules. However, in the concept of public speaking, grammar can be used to avoid mistakes and misunderstanding, so that, the messages are delivered correctly and the targets are reached purposely. Here, the writer divides the discussion of the grammar usage into two categories; they are the function of grammar in public speaking and the grammar awareness in public speaking. In addition, it is hoped that the readers consider to pay more attention toward the grammar before saying something, especially speaking in a public speaking context.